2010
DOI: 10.1074/jbc.m109.051557
|View full text |Cite
|
Sign up to set email alerts
|

RANKL-mediated Reactive Oxygen Species Pathway That Induces Long Lasting Ca2+ Oscillations Essential for Osteoclastogenesis

Abstract: RANKL (receptor activator of NF-B ligand) induces osteoclastogenesis by activating multiple signaling pathways in osteoclast precursor cells, chief among which is induction of long lasting oscillations in the intracellular concentration ofBone is a dynamic tissue that is constantly being remodeled. The remodeling process is a delicate balance between the activities of osteoblasts and osteoclasts. Interference with this balance results in serious human pathologies that affect bone integrity. Tipping the balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 45 publications
8
160
1
2
Order By: Relevance
“…54 Thus, following stimulation with RANKL, the pre-osteoclasts increase intracellular ROS by activation of NADPH oxidase (Nox) homologs or by increased mitochondria ROS production, which subsequently induced long lasting Ca 2+ oscillations. [54][55][56] In the present study both intracellular ROS and Ca 2+ content of osteoclast-like cells cultured on nano-HA disks and nano-SiHA disks were analyzed by Flow Cytometry and higher values of both parameters were obtained in cells cultured on nano-SiHA than on nano-HA ( Fig. 9B and 9C).…”
Section: Intracellular Ros and Camentioning
confidence: 99%
“…54 Thus, following stimulation with RANKL, the pre-osteoclasts increase intracellular ROS by activation of NADPH oxidase (Nox) homologs or by increased mitochondria ROS production, which subsequently induced long lasting Ca 2+ oscillations. [54][55][56] In the present study both intracellular ROS and Ca 2+ content of osteoclast-like cells cultured on nano-HA disks and nano-SiHA disks were analyzed by Flow Cytometry and higher values of both parameters were obtained in cells cultured on nano-SiHA than on nano-HA ( Fig. 9B and 9C).…”
Section: Intracellular Ros and Camentioning
confidence: 99%
“…However, the oscillations of calcium was not determined by their study. Long time lasting ROS production induced by RANKL is reported to mediate Ca 2+ oscillations and essential for osteoclast precursor differentiation [25], thus intracellular ROS level is probably involved in the promotion of TNF-a on calcium oscillation. Production of ROS associates to signals mediated by TNF-a [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that long term ROS production induced by RANKL mediates the Ca 2+ oscillations and regulates osteoclast differentiation [25]. TNF-a targets molecules which regulate calcium signaling.…”
Section: Tnf-a Promotes Rankl-induced Osteoclastogenesis Not Through mentioning
confidence: 99%
“…A previous investigator described that HPC attached to both the tooth surface and soft [33][34][35] ; however, NO is a reactive oxygen species (ROSs), which play a very important role in providing protection against bacterial infection; however, surplus ROSs cause cell damage 36,37) . From the point of view of bone remodeling or bone regeneration, ROSs act on the differentiation and activation of osteoclasts [38][39][40] . Since NO is supplied by arginine, the arginine level in gingival crevicular fluid from patients with chronic periodontitis is much higher than from a periodontally healthy group 41) .…”
Section: Discussionmentioning
confidence: 99%